2010
DOI: 10.1002/crat.201000097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature programmes on protein crystallisation

Abstract: Varying the temperature has been proven to be beneficial for improving the screening efficiency of protein crystallisation, and thus a crystallisation screening strategy based on this phenomenon can be developed. Such a temperature varying strategy can be applied in practical crystallisation screening, however, there are no guidelines for determining what temperature programme should be utilised. It is therefore necessary to investigate how the temperature programme affects the crystallisation process, so as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…We extracted the data for reproducibility tests of three proteins (lysozyme, proteinase K, and concanavalin A) from our previous publication [34] and carried out a new crystallization reproducibility test of α -chymotrypsinogen A(II). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We extracted the data for reproducibility tests of three proteins (lysozyme, proteinase K, and concanavalin A) from our previous publication [34] and carried out a new crystallization reproducibility test of α -chymotrypsinogen A(II). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent publications, we have already presented some reproducibility studies at two temperatures (277K and 293K) [34] , which can be used in the current study to show the trend of crystallization success rate versus the temperature. We extracted the data for reproducibility tests of three proteins (lysozyme, proteinase K, and concanavalin A) from our previous publication [34] and carried out a new crystallization reproducibility test of α -chymotrypsinogen A(II). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggest that some excipients can tolerate heat and absorb heat stress, not the protein included with those excipients.A study byDourado et al (42) showed that Eudragit® L-100 which has a very similar chemical structure to the one used in this study (Kollicoat® MAE 30 DP) can form weak bound conjugates with proteins(38). Kollicoat® MAE 30 DP (Fig1b) contains several methyl groups in its molecular structure.…”
mentioning
confidence: 92%
“…Therefore, many efforts have been made to increase the sample size and also to decrease the time required. Towards this end, many methods have been proposed, including the grid screen and incomplete factorial approaches [14][15][16], controlling the physical parameters such as the temperature [17,18], hydrodynamic field [19], electric field [20][21][22], magnetic field [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], and electromagnetic field [27,39,40] Despite various trials, obtaining a single crystalline outcome remains a challenge for some proteins owing to their low crystallization ability that prevents screening. In general, experimental parameters such as temperature, pH, and pressure, which are thought to be easily accessible, are selected.…”
Section: Introductionmentioning
confidence: 99%